Prevalence and Antibacterial Susceptibility of Selected Bacteria in the Urine of Biology Students at Tai Solarin University of Education - Ojo Folasade Tinuade, Sebiomo Adewole & (Covenant Journal of Physical and Life Sciences, 2019)
Urinary tract infection is a condition where one or more urinary structures become infected by the presence and growth of microorganisms that overcome the structures. This research work investigated the prevalence and antibacterial susceptibility of selected bacteria in the urine of biology students of Tai Solarin University of Education, Ijagun, Ogun State, Nigeria. Demographic survey of the students was determined. A 30 morse gauge, 3.26 mm calibrated wire loop capable of delivering 0.001 ml of urine was used for culturing on Blood Agar and MacConkey agar. The culture plates were incubated aerobically at 37˚C for 24 hours. Antibiotic susceptibility testing of the isolated test organisms was determined. Twenty-two percent of the respondents’ used antibiotic in the past 14 days while 78% of the respondents did not use antibiotics in the past 14 days. All the twenty-five female students tested for the presence of Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae in their urine tested positive to these pathogenic bacteria, although some in asymptomatic form. The highest Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae, counts of 2.41±0.00 × 105 CFU/ml, 5.59±0.00 × 105 CFU/ml and 1.86±0.00 105 CFU/ml respectively were obtained in the urine samples of the female and male students. The highest Total Bacteria count of 4.77±0.00 × 105 CFU/ml was obtained in the female urine samples. Gentamicin showed highest zone of inhibition in K. pneumonia culture plateswith a mean value of 2.83 mm followed by erythromycin (2.51 mm) and ampicillin (2.48 mm).